Principles of Formation of Foreign Language Communicative Competence among Future Officers of Rocket and Artillery Armament - Bhinder, Nataliya (Pedagogical Discourse, 2022)
The aim of the article is to outline the principles of formation of foreign language competence among future officers of rocket and artillery armament and to classify them on the basis of their typical features. While studying the problem, we have analyzed the process of formation of foreign language competence among future officers of rocket and artillery armament in scientific pedagogical and psychological literature. Also, we have defined the notion of the learning principle and explained the importance of appropriate selection of learning principles while organizing the educational process at the higher military educational establishment. We have found that learning principles means certain recommendations regulating pedagogic activity of instructor at the higher military educational establishment and the whole educational process considering peculiarities of professional training of future military specialists. We have proved that the process of formation of foreign language competence among future officers of rocket and artillery armament occurs according to basic principles that determine its content, organizational forms and teaching methods. Besides, we have classified the principles of formation of foreign language competence among future officers of rocket and artillery armament and we have found that there three groups of these principles – general didactical principles, linguistic and professional principles and methodical principles. We have explained their interrelation and influence upon the enhancement of levels of formation of foreign language competence among future officers of rocket and artillery armament. Also, we have outlined the ways of realization of these principles in the process of language training at the higher militray educational establishment.